Perception and coping strategies regarding the menstrual cycle: A questionnaire-based crosssectional study in elite female athletes during the 2022 European Championships - Wagner, J.; Schlicht, T.; Dandrieux, P.; Edouard, P.; Charpy, S.; Wurm, M.; Hollander, K.; Zyskowski, M. (Deutsche Zeitschrift für Sportmedizin, 2023)
Background: The menstrual cycle can influence sports performance and injury risks in competitive female athletes. However, there is a need to better explore how this is perceived by athletes. We aimed to explore how elite female athletes perceive and manage their menstrual cycle. › Methods: All female athletes who competed at the 2022 European Championships in Munich between 11th and 21st August 2022 in Athletics, Beach Volleyball, Canoe Sprint, Cycling, Gymnastics, Rowing, Table Tennis, and Triathlon were invited to answer a questionnaire on how they feel during the menstrual cycle, where they get advice and how they deal with it in training and competition. › Results: Sixty-seven female athletes (mean age 24.7 ± 4.8 years) from all contested sports answered the questionnaire. A majority (89.6%) reported having a regular menstruation cycle. At least one missed menstruation due to too much training was reported in 44.8%. For 49.3% of athletes, their menstruation had a negative impact on training. Only 38.8% felt normal during their menstruation and 46.2% felt uncomfortable. Regarding information on how to manage the menstrual cycle, 35.0% reported that they manage it by themselves, 14.6% get information from teammates, 14.6% from family, and only 5.8% from their team doctors. More than half of the athletes (58.2%) wanted information from coaches, 67.2% from team doctors, and 46.5% from sports federations. › Conclusion: The results showed that menstruation has an impact on athletes` health and performance. Further, most of them have to deal with the menstrual cycle by themselves. Sports federations, team doctors, and coaches have to establish educational programs on how to manage the menstrual cycle in training or competitions.